Effect of radiotherapy on the differentiation and osteogenic activity of mesenchymal stem cells on dental implants - Costa, Fernanda Herrera da; Dutra, Mateus José; Vasconcellos, Luana Marotta Reis de; Vegian, Mariana Raquel da Cruz; Silva, Camila Duarte da; Santos, Hanna Flávia Santana dos; Federico, Claudio Antonio; Prado, Renata Falchete do; Tango, Rubens Nisie; Kaminagakura, Estela (Brazilian Dental Science, 2023)
Objective: to evaluate the differentiation and gene expression of transcripts related to osteogenesis in a primaryculture of Mesenchymal Stem Cells (MSCs) derived from rat femurs submitted to radiotherapy and the installationof pure titanium implants. Material and Methods: fifty-four rats received titanium implants in both femurs andwere divided into three groups: Control: implant surgery (C); Implant + immediate irradiation (IrI), and Implant+ late irradiation (IrL). Euthanasia occurred 3, 14, and 49 days after surgery. The bone marrow MSCs from thefemurs were isolated and cultivated. The cell viability, total protein content, alkaline phosphatase (ALP) activity,and the formation of mineralization nodules and cellular genotoxicity were analyzed. The gene expression ofAlkaline Phosphatase (phoA), Collagen 1 (COL1), Runt-related transcription factor 2 (RUNX2), Osterix (OSX),Osteopontin (OPN), Integrin B1 (ITGB1), Bone Sialoprotein (BSP), Osteonectin (SPARC), Osteocalcin (Bglap),Transforming Growth Factor B-type (TGF-B), Granulocyte-Macrophage Colony Stimulating Factor (GM-CSF),Interleukin-6 (IL-6), Apolipoprotein E (APOE) and Prostaglandin E2 synthase (PGE2) were evaluated by qRTPCR.Results: ionizing radiation suppresses the gene expression of essential transcripts for bone regeneration,as well as cellular viability, as observed in the IrI and IrL groups. Conclusion: although this can lead to the lossof osseointegration and failure of the implant, the MSCs showed more activity at 49 days than at 3 and 14 days.KEYWORDSCancer treatment protocol; Osseointegration; Osteogenesis; Bone regeneration; Dental implants.